Fostering Students Motivation through Teachers Verbal Reinforcement: Insights from an Indonesian EFL Classroom - Kurniawan Hamid; La Sunra; Amra Aryani (English Education Department, 2026)
This study investigates how teachers’ verbal reinforcement influences students’ motivation to learn English at SMPN 40 Makassar. Employing a descriptive qualitative design, data were gathered through six classroom observations, semi-structured interviews with three English teachers and seven eighth-grade students, and documentation. The findings reveal that verbal reinforcement expressed through praise, affirmation, positive feedback, and personalization significantly enhances students’ motivation, confidence, and participation. Teachers’ consistent and context-sensitive use of encouraging language reduced anxiety, promoted active engagement, and fostered long-term interest in English learning. Students reported feeling recognized and supported when their efforts were acknowledged verbally, even in cases of partial or incorrect responses. The study concludes that authentic verbal reinforcement not only strengthens students’ intrinsic motivation but also functions as an affective pedagogical strategy that nurtures emotional connection and communicative confidence in EFL classrooms. Theoretically, the study contributes to understanding how verbal reinforcement, viewed through Self-Determination and Growth Mindset frameworks, operates as a motivational mechanism within teacher-student interactions.